Five new species of Tetranychidae (Acarina, Prostigmata) from south Tunisian oasis areas - Auger, Philippe; Ben Chaaban, Samah; Grissa, Kaouthar Lebdi; Khoualdia, Othman; Flechtmann, Carlos H. W. (Zootaxa, 2009)
In this paper we present the description of five new species of tetranychid mites collected in south Tunisian oasis areas. These are: Bryobia alveolata sp. nov., Aplonobia crispipilis sp. nov., Petrobia (Petrobia) carthagensis sp. nov., Petrobia (Petrobia) pseudotetranychina sp. nov. and Tetranychus (Tetranychus) atriplexi sp. nov. The notion of dorsal tubercles used to separate the sub-genera Tetranychina from Petrobia sensu stricto and Mesotetranychus among the genus Petrobia is also discussed.